10.61533 ANALISIS PENGARUH PERILAKU KONSUMEN GENERASI MILENIAL TERHADAP PRODUKTIVITAS UMKM DALAM MEWUJUDKAN EKONOMI BERKELANJUTAN DAN INKLUSIF DI KOTA PANGKALPINANG - David Andrezen Tjakra; Rizal R. Manullang; Medinal (Jurnal Ilmiah Niaga Bisnis Elektronik, 2026)
This study aims to analyze the influence of millennial consumer behavior on the productivity of Micro, Small, and Medium Enterprises (MSMEs) in order to realize a sustainable and inclusive economy in Pangkalpinang City. This study uses a quantitative approach with a survey method involving 100 millennial consumer respondents in Pangkalpinang City. Data analysis was conducted using multiple linear regression to determine the relationship between millennial consumer behavior and MSME productivity using the JASP for Windows program. The results of the data analysis show that cultural factors have a positive and significant effect on MSME productivity in Pangkalpinang City with a p-value of 0.002 < 0.05 and tcount (3.174) > ttable (1.66088). There is a positive and significant influence between social factors and MSME productivity in Pangkalpinang City with a p-value of 0.010 < 0.05 and tcount (2.638) > ttable (1.66088). Likewise, personal factors have a positive and significant effect on MSME productivity in Pangkalpinang City with a p-value of 0.001 < 0.05 and tcount (6.660) > ttable (1.66088). Simultaneously, cultural, social, and personal factors have a positive and significant effect on MSME productivity in Pangkalpinang City with a p-value of 0.001 < 0.05 and fcount (31.333) > ftable (2.70).